BβArg448Lys polymorphism is associated with altered fibrin clot structure and fibrinolysis in type 2 diabetes - Greenhalgh, Katie A.; Strachan, Mark W.; Alzahrani, Saad; Baxter, Paul D.; Standeven, Kristina F.; Storey, Robert F.; Ariens, Robert A. S.; Grant, Peter J.; Price, Jackie F.; Ajjan, Ramzi A. (Thrombosis and Haemostasis, 2017)
Both type 2 diabetes (T2DM) and Bß448Lys variant of fibrinogen are associated with dense fibrin clots, impaired fibrinolysis and increased cardiovascular risk. It was our objective to investigate whether BßArg448Lys adds to vascular risk by modulating fibrin network structure and/or fibrinolysis in diabetes. The primary aim was to study effects of BßArg448Lys on fibrin network characteristics in T2DM. Secondary aims investigated interactions between gender and BßArg448Lys substitution in relation to fibrin clot properties and vascular disease. Genotyping for BßArg448Lys and dynamic clot studies were carried out on 822 T2DM patients enrolled in the Edinburgh Type 2 Diabetes Study. Turbidimetric assays of individual plasma samples analysed fibrin clot characteristics with additional experiments conducted on clots made from purified fibrinogen, further examined by confocal and electron microscopy. Plasma clot lysis time in Bß448Lys was longer than Bß448Arg variant (mean ± SD; 763 ± 322 and 719 ± 351 seconds [s], respectively; p<0.05). Clots made from plasma-purified fibrinogen of individuals with Arg/Arg, Arg/Lys and Lys/Lys genotypes showed differences in fibre thickness (46.75 ± 8.07, 38.40 ± 6.04 and 25 ± 4.99 nm, respectively; p<0.001) and clot lysis time (419 ± 64, 442 ± 87 and 517 ± 65 s, respectively; p=0.02), directly implicating the polymorphism in the observed changes. Women with Bß448Lys genotype had increased risk of cerebrovascular events and were younger compared with Bß448Arg variant (67.2 ± 4.0 and 68.2 ± 4.4 years, respectively; p=0.035). In conclusion, fibrinogen Bβ448Lys variant is associated with thrombotic fibrin clots in diabetes independently of traditional risk factors. Prospective studies are warranted to fully understand the role of BβArg448Lys in predisposition to vascular ischaemia in T2DM with the potential to develop individualised antithrombotic management strategies.
Keywords: Diabetes Mellitus; fibrinogen; genetic polymorphism; thrombosis; vascular diseases